An algorithm for G2 offset approximation based on circle approximation by G2 quadratic spline. (April 2016) - Kim, Soo Won; Bae, Sung Chul; Ahn, Young Joon
Abstract: We present a method for G 2 approximation of offset curves using G 2 quadratic spline approximation of circular arc. An algorithm for the approximation method is presented and is applied to some numerical examples.